IDENTIFICATION OF EMISSION SOURCES BASED ON CHEMICAL COMPOSITION OF PARTICLES AS A BASIS FOR SELECTION OF AIR POLLUTION CONTROL TECHNOLOGY - Muhammad Diva, Thareq
East Jakarta is one of the cities in Indonesia that generates high concentrations of particulate matter (PM2.5). This is attributed to the increasing population density in East Jakarta, which grows by approximately 1.42% annually, potentially contributing to PM2.5 emissions from various sources. Research on the identification of pollution sources and recommendations for air pollution control in this area is urgently needed. PM2.5 samples were measured using a SuperSASS instrument for 24-hour periods every three days during the measurement period from October 18, 2023, to May 27, 2024. Teflon filters were utilized to determine PM2.5 mass concentrations, black carbon, trace elements, and dissolved ions, while quartz filters were used to analyze concentrations of organic carbon and elemental carbon. The average PM2.5 mass concentration was 39.13±16.7 µg/m³, with the contributions to PM2.5 distributed as follows: black carbon (18.12%), organic carbon (33.42%), elemental carbon (8.07%), trace elements (11.26%), and dissolved ions (19.25%). Positive Matrix Factorization (PMF) was applied to identify the dominant sources of air pollution. The PMF analysis revealed eight source factors, with transportation (48.8%) being the most dominant contributor. Based on this dominant source factor, it is recommended to conduct a comprehensive study on the selection of air pollution control devices for transportation sources, such as Diesel Particulate Filters (DPF) and Gasoline Particulate Filters (GPF), as a measure to address air pollution problems in East Jakarta.